지방자치단체의 재정건전성 강화를 위한 재정준칙의 도입 방안 검토 - 부산광역시 사례를 중심으로 - 이남국 (한국비교정부학보, 18(3), 2014)
Regardless of diverse efforts on fiscal decentralization since the launch of the autonomous local government system, capital bases of municipalities are still weak and the outlook is uncertain. In particular, municipalities’ accumulative debt has spiked as a result of a large scale local government bond issuing while overcoming the economic crisis in 2009 and thus, their financial deficit resulted from growth of expenditure and tax reduction is aggravating difficulties in local governments’ financial security. As a result, there is a widespread feeling that domestic municipalities can experience financial crises. Therefore, it is a time to discuss about possible central government’s measures between related experts. For this reason, this paper analyzed financial soundness and condition of Busan Metropolitan City and then suggested imposition of fiscal rules as a measure of strengthening financial soundness through efficient execution of scarce resource. The establishment of fiscal rule is expected to have a positive effect on local public finance by building a new budgetary routine and norms. The imposition of practical fiscal rules will have a major impact on local governments’ financial management. Hence, a prudence and systematic approach is required in the long-term along with collecting broad opinions. It is important to remember that the effectiveness of fiscal rule will depend on stakeholders: a local government, a local council and local residents. Continuous cooperation and effort will be required among the stakeholders based on the political agreement on fiscal rules. KCI Citation Count: 5